Increasing Learning Motivation through Kahoot as a Media Game Based Learning - Bahri, Aliem; Nurhidayah (Journal of Education Technology, 2024)
Students' learning motivation is often a challenge that needs to be overcome. Crucial factors such as limited interesting teaching methods and still using conventional methods, lack of variety in the learning process, and lack of use of innovative media. This research explores the use of Kahoot learning media in learning Indonesian in elementary schools as an effort to increase students' learning motivation. The aim of this research is to analyze the effectiveness of using Kahoot on students' learning motivation. The research method used was quantitative research involving fifth grade students. The experimental design used in this research is a quasi-experiment with a one group pretest post-test design. The data collection technique used was a test. Data collected from the test will be analyzed using Microsoft Excel software to determine the effectiveness of Kahoot learning media in increasing students' previous learning motivation. The results of this study showed that 64.29% of the pretest results were in the poor category, 28.57% were in the moderate category, and 7.14% were in the good category. Meanwhile, the post-test results showed that 28.57% of students were in the poor category, 35.71% of students were in the medium category, 21.43% of students were in the good category, 14.29% of students were in the very good category. So, it can be concluded that the use of Kahoot learning media is very effective in increasing students' learning motivation.